Evaluation of safety and efficacy of booster injections of hyaluronic acid in improving the facial skin quality. (30th May 2020) - Ayatollahi, Azin; Firooz, Alireza; Samadi, Aniseh
Abstract: Background: Skin boosting with small particles of hyaluronic acid (HA) is a new method of skin rejuvenation. Aim: Here, we aim to evaluate the efficacy and safety of booster injections of noncross‐linked HA in improving the facial skin quality. Methods: A total of 20 men and women age 40.15 ± 6.63 years were treated with 3 injections of noncross‐linked HA (1‐2 mL) with intervals of 3 weeks. Skin hydration and elasticity parameters were evaluated before intervention and 1 week and 4 months later. Facial skin improvement also evaluated using physician's global assessment score (PGA). Results: Skin hydration increased 1 week and 4 months after last treatment, ( P  > .05). Skin firmness (R0) reduced significantly at week 1 and month 4 ( P ‐value = .01 and .00). Skin‐tiring effect/fatigue (R3) showed significant decrease at week 1 and month 4 ( P ‐value = .01 and .00, respectively). Four months after last treatment skin gross elasticity (R2) and net elasticity (R5) also increased significantly ( P ‐value = .00). Physician's global assessment 1 week and 4 months after last treatment were 2.33 ± 0.76 and 1.35 ± 0.49 out of 4, respectively. Adverse effects were mostly transient and mild in severity. Conclusion: Booster therapy with HA is a safe and well‐tolerated procedure, and results in improvement in skin elasticity and relative increase in skin hydration.